Return of Results in Population Studies: How Do Participants Perceive Them?. (27th November 2020) - Nobile, Hélène; Borry, Pascal; Moldenhauer, Jennifer; Bergmann, Manuela M
Abstract: As a cornerstone of public health, epidemiology has lately undergone substantial changes enabled by, among other factors, the use of biobank infrastructures. In biobank-related research, the return of results to participants constitutes an important and complex ethical question. In this study, we qualitatively investigated how individuals perceive the results returned following their participation in cohort studies with biobanks. In our semi-structured interviews with 31 participants of two such German studies, we observed that some participants overestimate the nature of the personal information they will receive from the study. Although this misestimation does not seem to jeopardize the validity of the consent provided at recruitment, it may still represent a threat for participants' trust in research and thus their long-term commitment, crucial for such studies. We argue that such misestimation may have ethical consequences on the principles guiding the reflection on the return of results in biobank research, i.e. autonomy, beneficence, non-maleficence and reciprocity. We suggest that shifting from the idea of directly benefiting participants through the return of research results could help focusing on benefiting society as a whole, thereby increasing research trustworthiness of population-based studies using biobanks.